2017
DOI: 10.1007/s00705-017-3609-5
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of six full-length bean yellow mosaic virus genomes reveals phylogenetic diversity in India strains, suggesting subdivision of phylogenetic group-IV

Abstract: We report the complete genome sequence of five bean yellow mosaic virus (BYMV) isolates (CK-GL1, CK-GL3, CK-GL4, CK-GL5 and Vfaba2) that share 74.6-98.9% (nucleotide) and 81.5-99.1% (amino acid) identity with globally available BYMV sequences. Phylogenetic analysis clustered them specifically in BYMV phylogenetic group-IV within the existing nine groups. The CK-GL1, CK-GL2, CK-GL4 and CK-GL5 isolates formed a discrete cluster within group-IV. The present study suggests subdivision of group-IV into subgroup-IVa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In general, phylogenetic studies, based on the coat protein sequence of BYMV, established the existence of seven groups, a general one, with a wide hosts range, and six others named according to the original hosts (broad bean, canna, lupine, monocot , pea and W) (Wylie et al 2008). Further analysis based on the entire virus genome, revealed the presence of nine distinct groups, including the subdivision of the former general group into three new ones (Kehoe et al 2014), and recently Kaur et al (2018) suggested that the General group IV of the previous classification could be divided into two subgroups (IVa and IVb ). In this scenario, we generated additional phylogenetic analyses to further assess evolutionary relations of the detected virus among BYMV.…”
Section: Resultsmentioning
confidence: 99%
“…In general, phylogenetic studies, based on the coat protein sequence of BYMV, established the existence of seven groups, a general one, with a wide hosts range, and six others named according to the original hosts (broad bean, canna, lupine, monocot , pea and W) (Wylie et al 2008). Further analysis based on the entire virus genome, revealed the presence of nine distinct groups, including the subdivision of the former general group into three new ones (Kehoe et al 2014), and recently Kaur et al (2018) suggested that the General group IV of the previous classification could be divided into two subgroups (IVa and IVb ). In this scenario, we generated additional phylogenetic analyses to further assess evolutionary relations of the detected virus among BYMV.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue culture has improved gladiolus in many ways, including somaclonal variation and genetic stability [51,185], disease-free planting material selection in vitro [186][187][188], protoplast and somatic hybridization [189,190], synthetic seed technology [191,192], and in vitro mutagenesis [193]. Genetic transformation has been used in a number of reports to create transgenic gladiolus plants [24,[194][195][196].…”
Section: Insights and New Technologies For In Vitro Culture Of Gladiolusmentioning
confidence: 99%
“…On the contrary, isolates in the general group were identified in wild and domesticated hosts of monocots and dicots [3]. Some members of the monocot group can infect dicotyledonous species from three families: Orchidaceae, Iridaceae, Gentianaceae [5][6][7][8][9]. As phylogenetic relationships among BYMV isolates correlate with their natural hosts, Wylie et al (2008) proposed seven BYMV phylogenetic groupings based on coat protein sequences and the original hosts of the isolates: (i) general group with a broad host range of monocots and dicots; (ii) broad bean group; (iii) canna group; (iv) lupine group; (v) monocot group; (vi) pea group; and (vii) one strain 'W' from L. albus [3].…”
Section: Introductionmentioning
confidence: 99%